Authority in the case of an Alliance: Questions from the management (2011)
Authority as a type of power is the characteristic selected by Weber([1922]1997) for describing the business enterprise. The New InstitutionalEconomics (NIE) has recognized authority as the explanation for theexistence of the firms because it permits lowering coordination costsif compared with those of the market. Today, cooperation agreementsor alliances are common and some New Institutional Economists haveconsidered the costs of structuring the contracts that make them possiblebut they have left authority behind and with it, the coordinationof activities in those alliances where no new firm is constituted. Thissubject is the one that is considered, and the analysis of one case is thesource for the different questions asked. In the case studied, two parallelauthority structures leave areas in which authority becomes diffuse andcoordination debilitates.